Erratum: "Band gap tuning of Ni1−xMgxO films by radio-frequency sputter deposition for deep-ultraviolet photodetectors". (2nd February 2016) - Nishitani, Hiroki; Ohta, Kohei; Kitano, Sosuke; Hamano, Ryosuke; Inada, Mitsuru; Shimizu, Tomohiro; Shingubara, Shoso; Kozuka, Hiromitsu; Saitoh, Tadashi
Abstract :